Between Hebrew and Arabic poetry : studies in Spanish medieval Hebrew poetry - Tobi, Joseph (Medieval and Renaissance authors and texts, 2010)
The basic concept of this book is that in spite of the borrowed Arabic poetical values, medieval Hebrew poetry stubbornly distanced itself from Arabic poetry. The conclusive result of an in-depth comparative examination is that Hebrew poetry combined sele.